Distinct Encoding of Reward and Aversion by Peptidergic BNST Inputs to the VTA - Soden, Marta E.; Yee, Joshua X.; Cuevas, Beatriz; Rastani, Ariana; Elum, Jordan; Zweifel, Larry S. (Frontiers in Neural Circuits, 2022)
Neuropeptides play an important role in modulating mesolimbic system function. However, while synaptic inputs to the ventral tegmental area (VTA) have been extensively mapped, the sources of many neuropeptides are not well resolved. Here, we mapped the anatomical locations of three neuropeptide inputs to the VTA: neurotensin (NTS), corticotrophin releasing factor (CRF), and neurokinin B (NkB). Among numerous labeled inputs we identified the bed nucleus of the stria terminalis (BNST) as a major source of all three peptides, containing similar numbers of NTS, CRF, and NkB VTA projection neurons. Approximately 50% of BNST to VTA inputs co-expressed two or more of the peptides examined. Consistent with this expression pattern, analysis of calcium dynamics in the terminals of these inputs in the VTA revealed both common and distinct patterns of activation during appetitive and aversive conditioning. These data demonstrate additional diversification of the mesolimbic dopamine system through partially overlapping neuropeptidergic inputs.